Early Age Sex Identification in Date Palm (Phoenix dactylifera) - Khanum, Plosha; Ali Khan, Asif; Ahmad Khan, Iqrar; Khan, Zulqurnain (Journal of Agriculture and Biology, 2025)
The date palm is a widely cultivated important fruit crop in the world's dry and semi-arid regions. Date palm plants are easily multiplied from seeds, suckers or through plant cell and tissue culture. Both seed grown and tissue cultured plants require 4-5 years of vegetative growth to attain physiological maturity and reach the first flowering stage. However, identifying the sex of the plants during the vegetative phase remains highly challenging. Sucker propagation, with known sex, is a slow method and increases the risk of disease transmission. Therefore, early sex determination in the date palm is essential for breeding programs and long-term production. Here, we present a study of morphological, physiological and biochemical traits of female and male suckers from selected genotypes (Medjool, Amber and Ajwa) at an early vegetative growth stage. The results indicated significant differences between male and female plants, although variation in morphological and physiological traits was inconsistent, making it difficult establish reliable criteria for the sex differentiation based on these parameters alone. Notably, the stomatal conductance showed clearly differences between male and female plants of the selected genotypes. Similarly, biochemical traits also indicated significant and consistent differences between the sexes. Secondly, evaluation of highly responsive traits, stomatal conductance, and concentrations of nitrogen (N), phosphorus (P) and potassium (K) were assessed on randomly selected seedlings. The results indicated that male seedlings had higher stomatal conductance compared to female seedlings of the selected genotypes, whereas female seedlings consistently showed higher concentration of NPK. The study suggests that stomatal conductance and concentration of NPK are practical indicators for early-stage sex determination in date palm. Developing and refining sex determination methodologies will provide enabling tools for date palm breeders in designing and planting orchards for enhanced economic productivity in the future.
Keywords: Ajwa; Amber; Medjool; Morphological; Physiological; Stomatal conductance